2013
DOI: 10.1186/1471-2458-13-803
|View full text |Cite
|
Sign up to set email alerts
|

The importance of illness duration, age at diagnosis and the year of diagnosis for labour participation chances of people with chronic illness: results of a nationwide panel-study in the Netherlands

Abstract: BackgroundCompared to participation rates among general populations, participation of people with chronic illness in the labour market lags behind. This is undesirable, both from the perspective of individuals’ well-being as from a macro-economic perspective for western countries where concerns exist about labour supply and sustainability of social security in the near future. To help develop successful policy measures to prevent early drop-out and support reintegration, we aimed to gain insight into the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
3
21
0
1
Order By: Relevance
“…This higher gap is in line with previous studies showing that the postdiagnosis years are critical in terms of the person’s employment situation[14,21,30]. Contrary to people with other chronic diseases, where a longer duration of illness is associated with a higher risk of work exits[41], HIV-individuals are at higher risk for being unemployed at the beginning of their illness, even though physical limitations due to HIV infection are likely to still be limited, with the exception of individuals who have already reached an advanced stage of HIV disease at the time of diagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…This higher gap is in line with previous studies showing that the postdiagnosis years are critical in terms of the person’s employment situation[14,21,30]. Contrary to people with other chronic diseases, where a longer duration of illness is associated with a higher risk of work exits[41], HIV-individuals are at higher risk for being unemployed at the beginning of their illness, even though physical limitations due to HIV infection are likely to still be limited, with the exception of individuals who have already reached an advanced stage of HIV disease at the time of diagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…For the purpose of this study, we used data from people diagnosed with one (or more) chronic disease(s) who were participating in the National Panel of people with Chronic illness or Disability (NPCD), a nationwide prospective panel-study in The Netherlands [16,17]. NPCD was set up in 2005 to provide information about the experiences and consequences of living with chronic illness or disability from the patient's perspective.…”
Section: Samplementioning
confidence: 99%
“…Studies have shown that many cancer survivors do return to work . However, the labour participation rate (ie, the proportion of the working‐age population actually participating in the labour market) is lower among cancer survivors than among the general population, and compared with healthy controls, they are more likely to be unemployed . Cancer survivors who are employed usually work less hours than they did before their diagnosis .…”
Section: Introductionmentioning
confidence: 99%